(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
Vegetable oils play a key role in the food industry, and their consumer properties directly depend on the level and approach to refining. This article is dedicated to current trends in improving vegetable oil refining technologies, with a focus on applying innovative approaches such as biological methods, advanced technologies, and digitalization through AI and IoT. The combination of intelligent control systems, biotechnologies, and sensory networks leads to improved product quality, optimization of energy and material resources, and creation of a more environmentally friendly production process.